Management and Distribution of Course Catalogues with bolognaT3 - Eicker, Stefan; Schuler, J. Peter M.; Schuler, Peter M. (14th International Conference of European University Information Systems (EUNIS 2008), 2008)
1. EXECUTIVE SUMMARY This paper addresses the problems in information management on modularized courses in an interdisciplinary working department. After this, the general system design goals of bolognaT3 are introduced, which is a web based, centralized system for the management of course catalogues at the Faculty of Business Administration and Economics at the University of Duisburg-Essen. The success factors of the system and the rollout-project conclude the article. 1.1. Background Universities in Europe and especially in Germany are facing new conditions due to the Bologna process and the introduction of tuition fees. The Bologna process – intending to make the degrees of universities comparable – requires new structures for study programmes. The introduction of tuition fees – intending to lift the quality of the education by financing a portion of the costs through students – makes students to customers. The first causes a higher need for information guiding students and staff to the new way of studying. The second causes students to request better services and correct information anywhere and anytime. The competition between universities in Europe is hereby no longer only about reputation and academics but also on student service and the use of modern information technologies. The design of study programmes and academics in German universities are under decentralise control of the departments. The need to create new study courses and to change the structure and content of existing ones results in a high information demand by the committees responsible. The necessary information is often neither available in a central system nor in a formal matter. Often enough some of the information is hidden inside exam regulations at the exam office or inside the content of a lecture. Once the information is collected it is seldom kept up to date, because there is no possibility to easily look up which information is used where. Especially in departments with interdisciplinary courses which make use of the exchangeability of course modules there is a need to overcome problems of redundancy and out-dated information. 1.2. Conclusions Existing university systems and processes did not fit the need for structured information and information reuse on the one hand and detailed and configurable views on this information for web and print on the other hand. So a new system was necessary that would overcome the problems presented. The TYPO3 based system bolognaT3 was chosen for this purpose.
Keywords: course catalogue; study programme; module; Bologna process; bolognaT3; TYPO3